Effects of Germination Time and Varieties of Unmilled Rice on Blood Cholesterol in Sprague-Dawley Male Rats - Roohinejad, Shahin (2009)
Brown rice (unmilled rice) and pre-germinated brown rice are known to contain various functional compounds such as γ-oryzanol, dietary fiber and γ-aminobutyric acid (GABA) with substantial benefits for human health. The objectives of this study were to investigate the effect of pre-germination time of different unmilled rice varieties on GABA composition, and evaluate the hypocholesterolemic properties of selected pre-germinated unmilled rice varieties containing different GABA levels in rats. The results revealed a high variation in GABA contents in different unmilled rice varieties. GABA contents in Malaysian unmilled rice seeds ranged 0.01 to 0.1 (mg/g). MRQ74 and MR 220 showed the highest GABA contents among thirty five Malaysian unmilled rice varieties analyzed; while MR 232 had the least GABA content. It was also concluded that the effect of pre-germination on GABA content clearly was dependent on unmilled rice variety and pre-germination times, thus reflecting the longer pre-germination time provided higher GABA concentration level. Moreover, it was revealed that the GABA contents in pre-germinated samples were dependent on the initial GABA content of its source. In this study, the hypocholesterolemic properties of selected pre-germinated unmilled rice varieties containing different GABA levels in rats were investigated. Hypercholesterolemia and elevation of LDL-Cholesterol were successfully ameliorated by most of the unmilled rice and pre-germinated unmilled rice diets. Germinated unmilled rice showed more cardioprotective effect than non-germinated unmilled rice in hypercholesterolemic rats. Moreover, it was found that longer germination times had better effect on lipid profile of hypercholesterolemic rats. In addition to lipid profile, the hypoglycemic effects of unmilled rice and pre-germinated unmilled rice were found to be remarkable. The significant (p < 0.05) main effects of unmilled rice variety, germination time and their interaction on lipid and glucose profile were observed in the present study. A negative correlation between GABA content and the serum levels of TC and a positive correlation between GABA content and HDL-C were observed. Conversely, no correlation was shown between GABA content and LDL-C, TG and glucose levels. Although GABA played a role for prediction of lipid profile changes, this study was not capable to show a causative effect for this component. Therefore further extensive investigations are needed to clarify the main chemical(s) responsible for hypocholesterolemic effect of unmilled rice and pre-germinated unmilled rice. This study recommends that the unmilled rice and pre-germinated unmilled rice with excellent functional properties can be used instead of polished rice in Malaysian diet.